Sancta Sanctis: Pentecostals, Holiness, and the Breaking of Bread - Black, Jonathan (Journal of pentecostal theology, 2021)
Abstract The concept of holiness has played a significant role in Pentecostal identity. Worship has also been a defining feature of Pentecostalism, and for British Pentecostals, the ultimate locus of worship was historically around the Lord’s Table at the weekly Breaking of Bread service. Here at the Table holiness and worship met in the presence of the Lord, and in that meeting of the two the Gifts of the Spirit flowed, healing was found at the Table, and the Spirit-filled gathered congregation were sent back out into the world, renewed and refreshed as witnesses of the living Lord. While the Breaking of Bread could involve either intense joy or tears of repentance, it constantly bore witness to the seriousness with which Pentecostals took the holiness of God and His sanctification of His people. This article draws on historic British Pentecostal Eucharistic worship in working towards a Pentecostal theological account of holiness.